Maṯnawī-i mīrang - Baḫtiyār Kākī, Muḥammad ibn Kamāl-ad-Dīn (Nawal Kišūr, 1890)
Narrative poem by an Indian Sufi saint. - Maṯnawī--long romance in verse consisting of diverse short stories with mystical themes.